ECONOMIC VALUE OF MANGROVE ECOSYSTEM IN TANGERANG REGENCY, BANTEN PROVINCE - Haryanti, Rinrin; Susanto, Handoko Adi; Arkham, Muhammad Nur (Jurnal Segara, 2025)
The mangrove ecosystem plays a strategic role in supporting the sustainability of coastal environments through the provision of ecosystem services, which offer both economic and ecological benefits to local communities. However, mangrove ecosystems are facing degradation and the threat of destruction, including in the coastal areas of Tangerang Regency. The value of these ecosystems is often not fully quantified in resource assessments, necessitating research on the economic valuation of mangrove ecosystems. This study employs a mixed-methods approach with a sequential exploratory design, utilizing a questionnaire as the research instrument. Respondent sampling was conducted using purposive sampling combined with surveys and snowball sampling techniques. The data analysis focused on valuing ecosystem services, such as economic valuation through a combination of travel cost methods, replacement cost, primary productivity of litter, and carbon stock estimation, to calculate the total value of mangrove ecosystem services in Tangerang Regency. The results of the analysis show that the economic value of the ecosystem in this area amounts to IDR 52,005,917,307 per year, which is a combination of provisioning, regulating, cultural, and supporting services. Overall, this value is considered undervalued when compared to similar studies in Rembang, which reported IDR 85,166,427,218 per year, but overvalued when compared to Karawang, which reported IDR 2,528,000,709. These differences are influenced by factors such as mangrove area, ecological condition, productivity levels, and the parameters used in the calculations. This finding underscores the need for sustainable mangrove management and conservation to optimize both its economic and ecological benefits, while simultaneously enhancing coastal resilience against the threats of climate change and environmental degradation.